Konsep Uang Digital Di Aplikasi Dana Perspektif Hukum Ekonomi Syariah - Izzan, Ahmad; Piandi, Andri (STAI Al Musaddadiyah Garut, 2022)
Digital fund applications are among the companies providing digital-based financial services currently favored by the majority of the Indonesian population. These digital financial services are highly effective, efficient, and facilitate payment transactions commonly made by the public. However, the question arises whether these services are in line with Sharia principles. The formulation of the problem in this research is: 1. What is the concept of digital money in the DANA application? 2. What is the concept of digital money in the DANA application from the perspective of Sharia economic law? From these problem formulations, the objectives of this research are: 1. to understand the concept of digital money in the DANA application. 2. to understand the concept of digital money in the DANA application from the perspective of Sharia economic law. The method used in this thesis is field research. This research employs descriptive and analytical methods with a qualitative approach. Data collection techniques include observation, interviews, and documentation. Based on the research results, it can be concluded that the concept of digital money in the DANA application from the perspective of Sharia economic law is permissible because digital money does not violate Sharia rules in its usage or transactions as there are no elements of riba (usury), gharar (uncertainty), or maysir (gambling). Keywords: Sharia Economic Law, Digital Money, DANA Application